Marketing Strategy For Catfish Farming Products As A Culinary Business In Batu Kumbung Tourism Village, Lingsar District, West Lombok - Anak Agung Putu Gede Puja Anggara; Anak Agung Ketut Alit Pujawan (Devotion : Journal of Research and Community Service, 2026)
This study aims to analyze the marketing strategy of catfish (Clarias sp.) cultivation products as a culinary business in Batu Kumbung Tourism Village, Lingsar District, West Lombok. The research uses a descriptive qualitative approach with observation, interview, FGD, and documentation techniques. Data analysis is carried out using the SWOT method to identify internal and external factors of the business. The results of the study show that the main strength lies in the stable availability of raw materials and the innovation of processed products, while the weaknesses include limited capital and suboptimal digital marketing. Opportunities come from the development of tourism and information technology support, while threats include rising feed prices and business competition. The recommended strategy is the SO strategy through digital marketing optimization, product and packaging innovation, and educational tourism development. This strategy is expected to increase competitiveness and strengthen the village's identity as a fishery-based culinary destination.